Scarcity Pricing for Water Demand Management: A Case Study in Campina Grande -- Brazil - Araujo, Wanderbeg Correia de; Esquerre, Karla Patricia O.; Sahin, Oz; Silva, Brenner Biasi S. (Journal of Environmental Accounting and Management, 2026)
Despite being still little explored, tariff policies have a large potential to foster more efficient management of water resources, mainly in scarcity regions. Therefore, this paper proposes a model of water scarcity pricing (WSP), based on the storage average monthly data and historical average data of the volume of the reservoir between January 1996 and December 2017, besides the fixation coefficients of adjustments for each operational range and zones of accumulation of reservoir Epitácio Pessoa. The simulated results point to an annual percentage of significant reductions in water demand, mainly in years of low levels of water stocks in the reservoir, for example, 8% in the years 1998-2001 and almost 13% for 2016-2017. Moreover, it was also verified, through the water budget boundary (percentage of water bill over average residential income), that scarcity prices are accepted as socially just, because this rate is below the affordable index of 5%, as recommended by the World Bank. The WSP model has been created for the Water and Sewage Company that operates in Campina Grande, but might be easily implemented in all other regions that are supplied by surface reservoirs and operate under similar water scarcity conditions.